Anthoathecatae and Leptothecatae hydroids from Costa Rica (Cnidaria: Hydrozoa) - Kelmo, Francisco (2002)
This paper is the first taxonomic account of the hydroid orders Anthoathecatae and Leptothecatae from the Caribbean and Pacific coast of Costa Rica. All specimens are currently stored at the reference collection of the Museo de Zoología, Escuela de Biología, Universidad de Costa Rica. Sixteen hydroid species are recorded: Eudendrium carneum, Pennaria disticha, Acryptolaria longitheca, Plumularia floridana, Halopteris polymorpha, Aglaophenia dubia, Aglaophenia latecarinata, Lytocarpia tridentata, Macrorhynchia phillipina, Macrorhynchia sp., Clytia gracilis, Cnidoscyphus marginatus, Thyroscyphus ramosus, Dynamena disticha, Sertularella diaphana, and Tridentata distans. An extensive synonymy has been given for each species. A simplified taxonomic key is included, and illustrations and descriptions are provided for each species.